PATTERNS IN THE ACQUISITION OF IRREGULAR VERBS BY ENGLISH AS A FOREIGN LANGUAGE AND ENGLISH AS A SECOND LANGUAGE LEARNERS IN CAMEROON - Etengeneng, Dr. Ngasu Betek (African Journal of Education and Practice, 2020)
Purpose: This study sought answers on the patterns of acquisition of irregular verbs by second and foreign language learners of English in Cameroon. The premise is that in the process of acquiring irregular verbs, second and foreign language learners of English tend to use one form in place of the other, transfer rules, omit, substitute, overgeneralize and add rules. This study therefore embarked on a developmental and comparative paradigm to analyze morphological features in English as a Foreign Language (henceforth EFL) and English as a Second Language (henceforth ESL) learners' acquisition of irregular verbs in Cameroon. The scope was limited to a selection of some verbs of group 1, 2 and 3 irregular verbs, such as shut, split, hit, flee, bring, free, shine, tear, speak among others. Methodology: The survey research design was used and through simple random sampling, 900 students from six schools in Cameroon, of the Anglophone sub-system, and from the francophone sub-system, of secondary education were selected. Data was collected from completion tasks, multiple-choice questions and gap filling exercises, where the participants had to write out the present continuous, past tense and past perfect forms of irregular verbs; complete sentences by filling the blanks with the appropriate irregular verb form from given choices, and provide the appropriate form of a given irregular verb to complete a sentence. Data was analysed by identifying and mapping traceable frequency patterns of use and performing a comparative analysis of ESL and EFL users. Findings: The findings revealed that ESL and EFL learners of English possess some developmental features and they evolve as they move up the interlanguage continuum towards the target language forms. ESL learners produced more frequencies in form in the completion and gap filling tasks as opposed to the multiple choice task. Meanwhile, EFL learners produced more frequencies in gap filling tasks than ESL learners, and over generalized the "-ed" morpheme as a past tense marker to irregular verbs. Addition and substitution of forms were produced more with EFL learners. However, no matter the proficiency level, both ESL and EFL learners faced similar difficulties in the use of morphological forms in the process of acquiring irregular verbs. Unique contribution to theory, policy and practice: This paper informs on best practices for successful learning, specifically in the acquisition of irregular verbs by ESL and EFL learners of Cameroon. The interlanguage theory provides an explanation of the complexity of language learning within Cameroon's against its multiplicity of indigenous languages, thus recommending a rethink for novel approaches in the teaching of the English language in schools.